Updating Our View of Organelle Genome Nucleotide Landscape - Smith, David R. (Frontiers in Genetics, 2012)
Organelle genomes show remarkable variation in architecture and coding content, yet their nucleotide composition is relatively unvarying across the eukaryotic domain, with most having a high adenine and thymine (AT) content. Recent studies, however, have uncovered guanine and cytosine (GC)-rich mitochondrial and plastid genomes. These sequences come from a small but eclectic list of species, including certain green plants and animals. Here, I review GC-rich organelle DNAs and the insights they have provided into the evolution of nucleotide landscape. I emphasize that GC-biased mitochondrial and plastid DNAs are more widespread than once thought, sometimes occurring together in the same species, and suggest that the forces biasing their nucleotide content can differ both among and within lineages, and may be associated with specific genome architectural features and life history traits.